Effect of chlorocamphene on the isoenzyme spectrum of lactate dehydrogenase in rat serum and liver. - Kuz'minskaya, U A (1976)
Rats were used to study the general activity and the isoenzyme spectrum of lactate dehydrogenase (LDH) during single-instance and long-term introduction of polychlorocamphene. Total lactate dehydrogenase activity decreases in the liver during the single-instance introduction of half the LD50 (120 mg/kg). The isoenzyme spectrum of LDH is characterized by an increase in the quantity of LDH1, LDH2, and LDH3 and by a decrease in the amount of LDH4. The overall LDH activity does not change in blood serum. The isoform ratio changes insignificantly and LDH1 falls, but normalized 15 days after the introduction of the compound. Long-term introduction of polychlorocamphene at levels 1/100 the LD50 dose over 1.3 and 6 months causes a reduction in the overall LDH activity, both in the liver and in the serum. A decrease in the activity of the basic LDH isoenzyme of the liver (LDH5) and a sharp increase in LDH3 are characteristic for the isoenzyme spectrum of the liver. LDH1 and LDH4 decrease and LDH2 and LDH3 increase in blood serum. Beginning with the third month of polychlorocamphene introduction, LDH1 tends to return to normal levels. LDH2, LDH3, and LDH4 do return to normal levels, while LDH5 increases regularly. This results in a reduction of the number of H subunits and an increase of M subunits. This is characteristic of hypoxic states. On comparing the changes in the LDH enzymes of the liver and blood serum, it can be considered that the introduction of polychlorocamphene does not result in an increase in the permeability of the cellular membranes of the liver for LDH isoenzymes, while the observed isoenzyme spectrum shifts in blood serum are either the result of the biosynthesis of the isoforms of this enzyme changed by the compound or the result of the permeability for them of cells of other tissues.